A-site doping enabled higher-oxygen-vacancy cobalt-free layered perovskite cathode for higher-performing protonic ceramic fuel cells. Issue 24 (15th December 2022) - Teketel, Birkneh Sirak; Beshiwork, Bayu Admasu; Luo, Xiaoyan; Tian, Dong; Zhu, Shiyue; Desta, Halefom G.; Yang, Quan; Chen, Yonghong; Lin, Bin
Abstract: Cobalt-free layered perovskite as a promising mixed ionic electronic conductor cathode has shown outstanding performance in conventional oxygen-ion conducting solid oxide fuel cells (O–SOFCs), but not in next-generation proton-conducting solid oxide fuel cells (H–SOFCs) due to insufficient oxygen vacancy so far. We propose a facile A-site doping strategy to enable higher-oxygen-vacancy cobalt-free layered perovskite cathode for higher-performing protonic ceramic fuel cells at reduced temperatures. As proof of concept, two different typical A-site doping of mixed-rare-earth Nd and alkali-metal K in PrBaFe1.9 Zn0.1 O5+δ are chosen as potential H–SOFC cathode materials. Pr0.8 Nd0.2 BaFe1.9 Zn0.1 O5+δ (PNBFZ) and PrBa0.9 K0.1 Fe1.9 Zn0.1 O5+δ (PBKFZ) layered perovskite cathodes were synthesized using a nitrate-gel combustion method. Both PNBFZ and PBKFZ have a layered perovskite structure and are chemically compatible with protonic BaZr0.1 Ce0.7 Y0.2 O3−δ (BZCY) electrolyte. Both Nd and K doping dramatically improve the electrical conductivities under operation temperatures. Compared with PBKFZ, PNBFZ shows a lower average thermal expansion coefficient (TEC) of 13.9✕10 −6  K −1, being thermally compatible with the BZCY electrolyte without cracks. A-site doping in Fe-based layered perovskite cathodes promotes the single-cell output performance by around 100-26% at 550–700 °C, especially for the mixed-rare-earth doped PNBFZ with high peak power densities of 401–650 mW cm −2 .